2022
DOI: 10.1002/pits.22830
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of factors affecting depression in medical students

Abstract: Depression is more prevalent among medical students. Its level can be changed by different factors. The present study was designed and implemented in order to determine the path analysis of factors affecting depression in students of Qazvin University of Medical Sciences. This descriptive‐analytical study was conducted on 291 randomly selected students of Qazvin University of Medical Sciences in 2018. Data were collected using demographic characteristics questionnaires, Beck Depression Inventory and Gadzla Aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Prior research suggests that more satisfied students experience less stress as they feel they are making progress in their academic goals (Cygrymus and Lent, 2023). On the other hand, students are more vulnerable and face mental health challenges due to educational pressure, exam anxiety, and emotional issues that increase emotional fatigue and impact their well-being (Bahroodi et al, 2023). Evidence has shown that emotional fatigue is linked to students' performance and well-being (March-Amengual et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research suggests that more satisfied students experience less stress as they feel they are making progress in their academic goals (Cygrymus and Lent, 2023). On the other hand, students are more vulnerable and face mental health challenges due to educational pressure, exam anxiety, and emotional issues that increase emotional fatigue and impact their well-being (Bahroodi et al, 2023). Evidence has shown that emotional fatigue is linked to students' performance and well-being (March-Amengual et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This emotional exhaustion, which includes symptoms such as somatization, anxiety, and depression, is linked to a decrease in satisfaction and academic commitment, adversely affecting performance (Caballero et al, 2007;March-Amengual et al, 2022). Therefore, it is crucial to address the factors contributing to stress and depression to prevent their adverse effects (Bahroodi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%